Supportive care needs of the family caregivers of urostomy patients: a qualitative study - Kaixia Gao; Shaoguo Zhang; Jie Liu; Fang Zhang; Na Liu; Jiyan Dong; Tingting Zhang; Junping Gao; Sufang Qin; Junhong An; Xiaojuan Han (Scientific Reports)
Abstract Family caregivers play a vital role during the home care of urostomy patients by providing direct care and support. The role of family caregivers may extend to several years, even over ten years, in certain cases. In this process, the caregivers are impacted in various ways due to the patient’s conditions and may not be able to identify and address their own needs, which often get ignored and remain unfulfilled. The present study aimed to explore the supportive care needs of such family caregivers of urostomy patients. The method of qualitative research with the aid of purposive sampling was adopted in the present study. A semi-structured interview was conducted with 22 family caregivers of urostomy patients. Each interview lasted 60 min. Data analysis was conducted by employing the NVivo software for qualitative research and using a thematic approach. Four themes were identified: (i) Strong psychological and physical needs; (ii) Eagerness for information regarding the patient’s diseases; (iii) Need for social support; (iv) Necessity of spiritual support. Further, within these four themes, eight sub-themes were constructed using coders. The respondents reported that they felt equally under pressure as the urostomy patients they were caring for, although the medical staff appeared to be paying little attention to them. The medical staff paid greater attention to the patients, while the caregivers also required their help and support. The need for supportive care is quite common among the family caregivers of patients with urostomy. Medical staff should comprehensively understand the needs of the family caregivers of urostomy patients and then actively provide targeted psychological/physical/information/social/spiritual support to these caregivers. This would result in enhanced caregiving skills and reduced burden among these caregivers.